“Modulación de la respuesta inmune en juveniles de langosta de agua dulce (Cherax quadricarinatus) alimentados con mezclas”. - Mera Gómez, Henry Alejandro (2020)
The research was carried out at the “La María” Campus, belonging to the Quevedo State Technical University, in the aquaculture laboratory, for which 6 treatments with three repetitions were used in a DCA. Each of these treatments were structured around an experimental diet with different doses of probiotic mixtures (0 - control, 0.10, 0.20, 0.30, 0.40 y 0.50 mL). The main objective of this research was the evaluation of the immune replacement response in juvenile freshwater lobster (Cherax quadricarinatus) fed with probiotic mixtures, for this reason the results were expressed as follows, regarding the hypoxia variable which The best response was T4 with 76.19%, the lowest response was T0 with 9.56%. For the oxyhemocyanin variable, it was determined that there were no significant differences between the treatments, the p-value of 0.0644 being higher than expected from the F table. For total hemocytes, T4 with 11.74 was demonstrated as the best treatment and the lowest was T0 with 4.39. Regarding hyaline hemocyte cells, T3 performed better with 28.30% and the lowest amount was T1 with 15.50%. For expressed semi-granulocyte hemocyte cells, T0 with 70.79% performed better, and the lowest results resulted in T4 with 41.30%. In granulocyte hemocyte cells there were no significant differences. In the rate of phagocytosis it was demonstrated that the best treatment was T4 with a result of 38.28 proving to be significant among the other treatments. In the enzyme variable super oxide dismutase, T2 responded in a better way with 41.18 and T0 in a lesser way with 7.71. It is concluded that the results shown finally indicated that the 0.40ml treatment dose of probiotic mixtures improves the immune response of juveniles (Cherax quadricarinatus) for better production. Keywords: Antioxidant activity, food additive, phagocytosis, hemocytes, hypoxia